Social Stratification in Digital Learning: A Bibliometric Analysis of Self-Regulated Learning and Pedagogy via Biblioshiny (2016–June 2026) - Ridha Aulia; Ervin Endro Sasongko; Alamsyah Siregar; Maya Nur Anisa; A. Nururrochman Hidayatulloh (Sakura Digital Nusantara, 2026)
The digital transformation of global education has accelerated pedagogical shifts that prioritize students’ self-regulated learning (SRL) as a prerequisite for academic achievement. However, contemporary digital curricula frequently overlook social stratification and material disparities present in students’ home learning environments. This descriptive-quantitative bibliometric study maps thematic trends, critiques epistemic biases, and synthesizes global literature on the relationship between socioeconomic class, digital inequality, and students’ digital self-regulated learning agency from 2016 to June 2026. Utilizing the PRISMA protocol, 45 Scopus-indexed documents were analyzed with the Bibliometrix R-package via the Biblioshiny interface. Pierre Bourdieu’s framework of capital, habitus, and symbolic violence guided the examination of publication trends, geographical distribution, citation structures, collaboration patterns, co-keyword networks, and thematic evolution. The results indicate a 19.62% annual growth rate, with a marked increase in publication activity during the first half of 2026. China led in publication output (19 appearances) and citation visibility (182 citations), followed by the United States (10 publications; 178 citations) and Australia (5 publications; 104 citations). Indonesia ranked among the top five contributors in publication output but was absent from major citation distributions, highlighting citation invisibility despite publication visibility. Co-keyword and thematic evolution analyses identified two major shifts: the reduction of SRL’s theoretical depth to psychological, demographic, and administrative performance indicators, and the instrumentalization of SRL through artificial intelligence, adaptive learning technologies, and platform-based education. This study advances Critical SRL by demonstrating that digital learning agency constitutes a stratified form of digital cultural capital rather than solely an individual psychological capacity. The findings are pertinent to policymakers, curriculum designers, and educational technology developers in developing countries aiming to create class-sensitive and socially just digital learning systems.